The private and local business of parliament - Murphy, Joseph John (Dublin Statistical Society, 1856)
I will not attempt any detailed exposure of the vices of the system ; the rather as this has been admirably done by a writer in the Edinburgh Review for January, 1855, in an article entitled "Private Bill Legislation" which I will not spoil by attempting to condense. I will here speak only of the enormous expense it entails on the promoters of bills, especially when they meet with opposition. In the latter case the expense is so great, that it is by no means uncommon to oppose a bill on perfectly frivolous and untenable grounds, in hope that the promoters may find it cheaper to buy off opposition than to contest it. And who can tell how many useful enterprises are rendered impracticable, because they are too small to pay the expense of obtaining the necessary powers from Parliament? The Limited Liability Act does not meet this objection, for it affords no facilities for obtaining the power of compulsory purchase, which is equally necessary, in many cases, with that of the limited liability of shareholders. It is, besides, utterly unreasonable to expect members of Parliament to do the kind of work which is thrown on them by our system of private legislation. The expression private legislation is, in fact, a misnomer, a contradiction in terms. It is not legislation at all, but administration; and administrative work is not suited to Parliament.
Read May l9th, 1856
Keywords: Parliamentary legislation; 314.15